Phase II Study of Adjuvant Immunotherapy with the CSF-470 Vaccine Plus Bacillus Calmette–Guerin Plus Recombinant Human Granulocyte Macrophage-Colony Stimulating Factor vs Medium-Dose Interferon Alpha 2B in Stages IIB, IIC, and III Cutaneous Melanoma Patients: A Single Institution, Randomized Study - Mordoh, José; Pampena, María Betina; Aris, Mariana; Blanco, Paula Alejandra; Lombardo, Mónica; von Euw, Erika María; Mac Keon, Soledad; Yépez Crow, Michelle; Bravo, Alicia Inés; O’Connor, Juan Manuel; Orlando, Ana Gabriela; Ramello, Franco; et al. (Frontiers in Immunology, 2017)
The irradiated, allogeneic, cellular CSF-470 vaccine plus Bacillus Calmette–Guerin (BCG) and recombinant human granulocyte macrophage-colony stimulating factor (rhGM-CSF) is being tested against medium-dose IFN-α2b in stages IIB–III cutaneous melanoma (CM) patients (pts) after surgery in an open, randomized, Phase II/III study. We present the results of the Phase II part of the ongoing CASVAC-0401 study (ClinicalTrials.gov: NCT01729663). Thirty-one pts were randomized to the CSF-470 vaccine (n = 20) or to the IFN-α2b arm (n = 11). During the 2-year treatment, immunized pts should receive 13 vaccinations. On day 1 of each visit, 1.6 × 107 irradiated CSF-470 cells plus 106 colony-forming units BCG plus 100 µg rhGM-CSF were administered intradermally, followed on days 2–4 by 100 µg rhGM-CSF. IFN-α2b pts should receive 10 million units (MU)/day/5 days a week for 4 weeks; then 5 MU thrice weekly for 23 months. Toxicity and quality of life (QOL) were evaluated at each visit. With a mean and a maximum follow-up of 39.4 and 83 months, respectively, a significant benefit in the distant metastasis-free survival (DMFS) for CSF-470 was observed (p = 0.022). Immune monitoring showed an increase in antitumoral cellular and humoral response in vaccinated pts. CSF-470 was well tolerated; 20/20 pts presented grades 1–2 dermic reactions at the vaccination site; 3/20 pts presented grade 3 allergic reactions. Other adverse events (AEs) were grade 1. Pts in the IFN-α2b arm presented grades 2–3 hematological (7/11), hepatic (2/11), and cardiac (1/11) toxicity; AEs in 9/11 pts forced treatment interruptions. QOL was significantly superior in the vaccine arm (p < 0.0001). Our results suggest that CSF-470 vaccine plus BCG plus GM-CSF can significantly prolong, with lower toxicity, the DMFS of high-risk CM pts with respect to medium-dose IFN-α2b. The continuation of a Phase III part of the CASVAC-0401 study is encouraged.